Relationship Of Community's Perceptions And Attitude To People With Mental Disorders Case Study In Paringan Jenangan Village, Ponorogo - Eky Okviana Armyati vivi; Nurul Sri Wahyuni; Dian Laila Purwoningrum; Dwi Nurwulan Pravitasari (Saintika Medika, 2022)
Society is the people around us that have many varieties and cultures. The variety and culture are so many that various problems arise, one of which is People With Mental Disorders (ODGJ). People with mental disorders or ODGJ are one of the communities around us. Society always evaluates negatively and also alienates families with ODGJ. Based on the results of the study obtained data that of 50 respondents based on gender the perception of women is worse than men. Based on education for the Bachelor level, the perception is better than those who have graduated from elementary school. Based on the age of those aged over 40 years, the perception and attitude of the community is better towards ODGJ. Based on the results of the Rank-Speramen correlation test, the data obtained. So Ho is rejected, which means that there is a significant relationship between people's perceptions and attitudes towards people with mental disorders (ODGJ). The results of data analysis using the Spearman rank correlation statistical test are known to be rhit = 0.638. Because the correlation coefficient is positive, it means that perception is positively and significantly related to people's attitudes. So in this study it can be concluded that there is a relationship between people's perceptions and attitudes towards people with mental disorders. where if the perception is good, the attitude of the community towards ODGJ in Paringan Village, Jenangan sub-district is also good